(3OQ GdJJhjL HJYQjH eDGeQGJ GdRjLs - (3bGVj MSf Gdecj , MSf Hf eMeOs
(3ChdgG (B:s
(3GdMeO ddg (B: (3Ndb GdSehGJ hGdCQV hLYd GdXdeGJ hGdfhQ s
(3BNQgG (B:s
(3hgcPG hai eHOC GdJGQjN GdeGdci eVJ NeSeGFg hKeGfhf SfI ef Sfi GdTeShGddg JYGdi CYde s
(3JMJhi Ydi YOO ef GdLOGhds
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B288s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B33 s
Keywords: (3Gdadcs